The pattern pages emagazine (The Pattern Pages.)
Things have changed in the sewing industry over the last few years. Today, there’s so many exciting new independent pattern companies, and dressmaking bloggers out there, as well as the major commercial companies, but there’s no longer a magazine dedicated solely to dressmaking. We keep you up-to-date with the latest sewing pattern news, fashion trends for the seasons and how to replicate them in your sewing. We also have lots of sewing tips and advice form experts to help you make your own clothes look the best they can.